Structure-property relationship of polyester and palm oil polyols and their evaluation in solid polyurethanes - Tuan Ismail, Tuan Noor Maznee (2019)
Understanding on the structure-property relationship between raw materials and the resultant polyurethane (PU) products is very crucial, especially for PU formulators. PU formulation is a trade secret, therefore, in development of PU products for specific target applications and performances, skill and expertise are required. To gain these skill and expertise, a lot of formulations need to be done which definitely involve cost and very time-consuming. However, these problems can be minimized with an availability of a systematic study on structure-property relationship between raw materials and their resultant PU products. Therefore, a systematic study on structure-property relationship of polyester and palm oil-based polyols in solid polyurethanes (SPUs) were conducted. SPUs made from polyester and palm oil-based polyols were characterized in terms of physico-mechanical and thermal properties as well as their morphologies. It was found that, in azelate polyols, resilience and durability of SPUs can be optimized by selecting azelate polyols with odd carbon number in the linear diols and by using shorter chain linear diols. In 1,4- butanediol-based polyester polyols, these properties can also be achieved by selecting polyester polyols from dicarboxylic acids (n-DCAs) with odd carbon numbers. It was also found that, the SPUs with maximized material strengths can be obtained from polyester polyols with even carbon numbers in both linear diols and n-DCAs. Phase interaction through formation of hydrogen bondings was the contributing factor to the properties of SPUs observed. For SPUs made from palm olein-based polyols, there were no significant changes in properties of SPUs observed, with regards to different types of reactants used during ring-opening reaction of epoxide groups. Thus, the findings could provide a guidance to PU formulators to choose the right raw materials to be used in their formulations. Through suitable choice of raw materials, a huge range of PU products could be made. Therefore, the findings from this study could have practical significance in the selection and synthesis of polyester and palm oil-based polyols for PU applications.